2020
DOI: 10.1155/2020/7083415
|View full text |Cite|
|
Sign up to set email alerts
|

Schisandra Fruit Vinegar Lowers Lipid Profile in High‐Fat Diet Rats

Abstract: Hyperlipidemia and its associated obesity, hepatic steatosis, and NAFLD are worldwide problems. However, there is no ideal pharmacological treatment for these. Therefore, the complementary therapies that are both natural and safe have been focused. Healthy foods, such as fruit vinegar, may be one of the best choices. In this study, we made a special medicinal fruit vinegar, Schisandra fruit vinegar (SV), and examined its lipid-lowering effects and the underlying mechanisms in a high-fat diet rat model. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Beheshti et al reported that vinegar consumption reduced TG, TC and LDL-C levels in hyperlipidemia patients, and had no significant influence on HDL-C level ( Beheshti et al, 2013 ). Another study reported that schisandra vinegar significantly reduced serum TG, TC and LDL-C content, and increased HDL-C content in high-fat diet rats ( Yuan et al, 2020 ). In present study, SAV has no effects on blood lipids in normal mice.…”
Section: Resultsmentioning
confidence: 99%
“…Beheshti et al reported that vinegar consumption reduced TG, TC and LDL-C levels in hyperlipidemia patients, and had no significant influence on HDL-C level ( Beheshti et al, 2013 ). Another study reported that schisandra vinegar significantly reduced serum TG, TC and LDL-C content, and increased HDL-C content in high-fat diet rats ( Yuan et al, 2020 ). In present study, SAV has no effects on blood lipids in normal mice.…”
Section: Resultsmentioning
confidence: 99%
“…Fruit vinegar's blood-lipid-lowering benefits can be attributed, in large part, to its antioxidant and antiinflammatory properties (14,15). However, because different sources of carbs and microorganisms are used during the fermentation process, the bioactivities and health benefits of vinegar may vary (16). Currently, red dates, black dates, and green dates are the primary sources of jujube vinegar (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, because different sources of carbs and microorganisms are used during the fermentation process, the bioactivities and health benefits of vinegar may vary (16). Currently, red dates, black dates, and green dates are the primary sources of jujube vinegar (16,17). Caffeic acid, ferulic acid, flavonoid, and carotenoid comprise the bulk of jujube vinegar's biological functions (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The improved glycemic response is attributed to acetic acid, which has been demonstrated to reduce the digestive capacity of disaccharidases in vitro [7] and to enhance the clearance of glucose from the blood stream into muscle in vivo [4,8]. The lipid lowering mechanism of vinegar may relate to the upregulation of PPAR-α and its target genes acyl-CoA oxidase 1 and carnitine palmitoyltransferase I, and enhanced β-oxidation in the liver [9,10]. Possibly, bioactives in vinegar in concert with acetic acid initiate these effects [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The lipid lowering mechanism of vinegar may relate to the upregulation of PPAR-α and its target genes acyl-CoA oxidase 1 and carnitine palmitoyltransferase I, and enhanced β-oxidation in the liver [9,10]. Possibly, bioactives in vinegar in concert with acetic acid initiate these effects [9,10].…”
Section: Introductionmentioning
confidence: 99%